Performance evaluation of Khyber Pakhtunkhwa Rice Husk Ash (RHA) in improving mechanical behavior of cement. (10th July 2018) - Khan, Waheed; Shehzada, Khan; Bibi, Tayyaba; Ul Islam, Shams; Wali Khan, Sajjad
Highlights: Study of RHA in KPK at higher temperature. The chemical composition of RHA varies with source. RHA content up-to 15% increase the compressive and flexure strength at later ages. Incorporation of RHA in cement mortar inhibit the ASR. Burning of RHA at higher temperature transform amorphous silica to crystalline silica. Abstract: The rice husk (RH) as an agro-waste materials having low nutritional properties as a provender, when burnt under controlled temperature produce great quantity of Rice Husk Ash (RHA). The use of RHA as a supplementary cementitious materials have much importance in construction industry especially in the countries of high rice production. This paper discus the collection of rice husk (RH) from different regions of Khyber Pakhtunkhwa (KPK), the properties of Rice Husk Ash produced from these RH by different combustion methods of high temperature and their effect on mechanical behavior of cement. To evaluate the chemical composition and quantification of crystalline silica in RHA of various regions of KP, EDX and XRD tests were performed. Consistency, setting time, compressive, flexural strength and Alkali silica reaction tests were also performed for various replacement level of RHA i.e. 5%, 15% and 25% in cement paste and in mortar. Results show an obvious variation in the silica content with variation in sources. A partial transformation of amorphous silica to crystalline silica was observed at 800 °C (method A ) and mostly at a temperature of 1000 °C (method B ). RHA by method A and B, as a partial replacement of cement increase linearly the consistency and setting time but decrease the alkali silica reaction. Also the RHA by method A increased the compressive and flexural strength up-to 15% at later ages but a slight increase was observed up-to 5% replacement of RHA by method B .